Libifem® (Trigonella foenum-graecum) in conjunction with exercise on muscle strength, power, endurance, and body composition in females aged between 25 and 45 years - Rao, Amanda; Clayton, Paul; Briskey, David (Frontiers in Sports and Active Living, 2023)
Introduction This study examined the effects of Libifem® on exercise performance and body composition in females 25–45 years old. Methods Participants were randomized to three equal groups to consume: 600 mg Libifem®/day, 300 mg Libifem®/day or a placebo for 8 weeks. Participants completed a whole-body exercise program three times a week for 8 weeks. At baseline, week 4 and week 8, muscle strength and endurance, functional threshold power, body composition, and sex hormones were measured. At week 8, all three groups increased leg press 1RM compared to baseline. Results A significant difference between group treatment effect was seen for leg press at week 8 (p = 0.045), with the 600 mg Libifem® group significantly increasing their leg press 1RM compared to placebo (p = 0.014). The 600 mg Libifem® group significantly reduced their total fat mass (0.96 kg loss) from baseline compared to placebo group (0.09 kg gain). There was no significant difference in fat mass for the 300 mg Libifem® group (0.23 kg loss). The 600 mg Libifem® group had a significant increase in lean mass compared to both the 300 mg and placebo groups (p = 0.011 and 0.009, respectively). Discussion Overall, there were significant and dose-related changes in body composition and ergogenic parameters, comparable with previous findings in males. Clinical Trial Registration This trial was registered with the Australian and New Zealand Clinical Trials registry [ACTRN12618001538235].